2007
DOI: 10.1523/jneurosci.5308-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Slack and Slick KNaChannels Regulate the Accuracy of Timing of Auditory Neurons

Abstract: The Slack (sequence like a calcium-activated K channel) and Slick (sequence like an intermediate conductance K channel) genes, which encode sodium-activated K ϩ (K Na ) channels, are expressed at high levels in neurons of the medial nucleus of the trapezoid body (MNTB) in the auditory brainstem. These neurons lock their action potentials to incoming stimuli with a high degree of temporal precision. Channels with unitary properties similar to those of Slack and/or Slick channels, which are gated by [Na ϩ ] i an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 58 publications
7
130
0
Order By: Relevance
“…For short pulse stimulations, 2-ms duration currents of 800 pA with increasing frequency (from 50 to 300 Hz with increment of 50 Hz) were injected. Because the current injection is very short for short pulse stimulations, we found that only the large current (800 pA) can reliably induce the first AP in control neurons, consistent with previous studies (33)(34)(35).…”
supporting
confidence: 91%
“…For short pulse stimulations, 2-ms duration currents of 800 pA with increasing frequency (from 50 to 300 Hz with increment of 50 Hz) were injected. Because the current injection is very short for short pulse stimulations, we found that only the large current (800 pA) can reliably induce the first AP in control neurons, consistent with previous studies (33)(34)(35).…”
supporting
confidence: 91%
“…Unlike Slack channels, there is an ATP-binding site on the Slick COOH terminus (Bhattacharjee et al 2003). Bithionol, a bis-phenol compound known for its antiparastic actions, potently activates Slack currents (Yang et al 2007). Activation of PKC increases the amplitude of Slack-B currents and decreases the amplitude of Slick currents (Santi et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Quinidine is a very effective blocker of these channels in both expression systems and neurons (Bhattacharjee et al, 2003;Yang et al, 2006Yang et al, , 2007Milligan et al, 2014;Rizzo et al, 2016). It has been reported that quinidine ameliorated the symptoms of a patient with malignant migrating partial seizures in infancy, but because this agent blocks a wide variety of other channels, the mechanism is not known (Bearden et al, 2014).…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 99%
“…Experiments using excised patches demonstrate that application of 5 mM ATP or a nonhydrolyzable ATP analog reduced currents by ;80% and that mutation of this consensus site abolished the effect of ATP (Bhattacharjee et al, 2003). Moreover, ATP and a nonhydrolyzable analog were both found to suppress Na + -and Cl 2 -activated K + channels in excised patches from auditory brain stem neurons that express K Na 1.2 (Yang et al, 2007). In contrast, experiments with a K Na 1.2-GFP fusion construct expressed in HEK cells failed to find an effect of adding ATP to patch pipettes on current amplitude (Berg et al, 2007).…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 99%